Length–weight relationship, condition factor, sex ratio and size at first maturity of the blue‐spotted tilapia (Oreochromis leucostictus) in Lake Naivasha, Kenya. Issue 3 (21st August 2022) - Cishahayo, Laurent; Yongo, Edwine; Mutethya, Eunice; Waithaka, Edna; Ndayishimiye, Rose
Abstract: Oreochromis leucostictus is a commercially important tilapiine in Lake Naivasha, with its stocks having declined because of the effects of fishing, habitat degradation and pollution. The present study investigated its length–weight relationship, condition factor, sex ratio and maturity. Fish samples (233) were collected during 2017, with each fish measured (cm), weighed (g) and analysed for maturity in the laboratory. The mean (±SD) total length and weight were 21.3 ± 0.3 cm TL and 187.4 ± 8.3 g, respectively. The fish exhibited a negative allometric growth pattern ( b  = 2.33). The mean condition factor was 1.06, 0.99 and 1.04 for male, female and combined sexes, respectively. The condition factor was significantly higher in September (1.70 ± 0.15) and October (1.63 ± 0.15) than in other months. Males were significantly more dominant than females (male:female sex ratio = 2.19:1.0). Females (21.0 cm TL) matured at smaller lengths, compared to males (26.0 cm TL). Comparisons with earlier studies suggested the length–weight relationship, condition factor, sex ratio and size at first maturity of O. leucostictus in Lake Naivasha varied significantly from other tilapiines in various water bodies. The results of the present study provide insights into the biological attributes of O. leucostictus useful for its sustainable management.